Resettlement’s Renaissance: A Cautionary Advocacy - Labman, Shauna (Refuge: Canada's Journal on Refugees, 2007)
Arising out of UNHCR’s Global Consultations was a renewed emphasis on the role of resettlement as a protection tool, durable solution, and burden-sharing mechanism. Resettlement is a useful instrument for all three reasons enumerated by UNHCR. Its malleability, however, also makes it prone to manipulation. It can be, and has been, used by states to obfuscate an unwillingness to meet their international legal obligations through a replacement of refugee protection by migrant selection. The argument is made here for why resettlement is a necessary component of refugee protection, particularly in the current period of securitization following the events of 11 September 2001. This is followed by a discussion of the dangers of the abusive use of resettlement to the overall refugee protection scheme. Models for more structured resettlement are examined with a view to understanding what reform is needed. In conclusion, recommendations for resettlement reform are provided.